2001
DOI: 10.1209/epl/i2001-00557-x
|View full text |Cite
|
Sign up to set email alerts
|

Phase diagram of the Hubbard model: Beyond the dynamical mean field

Abstract: The Dynamical Cluster Approximation (DCA) is used to study non-local corrections to the dynamical mean field phase diagram of the two-dimensional Hubbard model. Regions of antiferromagnetic, d-wave superconducting, pseudo-gapped non-Fermi liquid, and Fermi liquid behaviors are found, in rough agreement with the generic phase diagram of the cuprates. The non-local fluctuations beyond the mean field both suppress the antiferromagnetism and mediate the superconductivity.Introduction The rich phenomenology of high… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
89
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(112 citation statements)
references
References 18 publications
21
89
2
Order By: Relevance
“…To better understand the failure of QMC calculations with fixed U = 8t to explain the observed ASWT, in Figure 4(a-b) we plot the DOS and the associated electron count calculated in QMC 8,9 . For ω c = 0.4 eV, close to the DOS minimum 38 , W UHB is in good agreement with the exact diagonalization results for the corresponding U = 8t, 39 blue stars in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…To better understand the failure of QMC calculations with fixed U = 8t to explain the observed ASWT, in Figure 4(a-b) we plot the DOS and the associated electron count calculated in QMC 8,9 . For ω c = 0.4 eV, close to the DOS minimum 38 , W UHB is in good agreement with the exact diagonalization results for the corresponding U = 8t, 39 blue stars in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have already shown that the Hubbard model treated within cluster DMFT on a 2 by 2 plaquette successfully describes many properties of the high temperature superconductors. For example the competition of antiferromagnetism and superconductivity [35][36][37][38][39] , the existence of a pseudogap at low doping [40][41][42][43][44][45][46] , and the formation of Fermi arcs 43,44,47,48 . These phenomena involve short range non local correlations.…”
Section: Introductionmentioning
confidence: 99%
“…(We refer to DCA/CDMFT/VCA collectively as Green's function cluster theories.) These pioneering works have suggested rich phenomenology in the phase diagram including metallic, antiferromagnetic, and d-wave (and other kinds of) superconducting phases, a pseudogap regime, inhomogeneous orders such as stripes, and charge, spin, and pairdensity waves, as well as phase separation [6,19,20,24,25,[27][28][29]32,35,[39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58]. However, as different numerical methods have yielded different pictures of the ground-state phase diagram, a precise quantitative picture of the ground-state phase diagram has yet to emerge.…”
mentioning
confidence: 99%